Contrasting Immunopathogenic and Therapeutic Roles of Granulocyte Colony-Stimulating Factor in Cancer - Annette J. Theron; Helen C. Steel; Bernardo L. Rapoport; Ronald Anderson (MDPI AG, 2020)
Tumor cells are particularly adept at exploiting the immunosuppressive potential of neutrophils as a strategy to achieve uncontrolled proliferation and spread. Recruitment of neutrophils, particularly those of an immature phenotype, known as granulocytic myeloid-derived suppressor cells, is achieved via the production of tumor-derived granulocyte colony-stimulating factor (G-CSF) and neutrophil-selective chemokines. This is not the only mechanism by which G-CSF contributes to tumor-mediated immunosuppression. In this context, the G-CSF receptor is expressed on various cells of the adaptive and innate immune systems and is associated with induction of T cell polarization towards the Th2 and regulatory T cell (Treg) phenotypes. In contrast to the potentially adverse effects of sustained, endogenous production of G-CSF by tumor cells, stringently controlled prophylactic administration of recombinant (r) G-CSF is now a widely practiced strategy in medical oncology to prevent, and in some cases treat, chemotherapy-induced severe neutropenia. Following an overview of the synthesis, structure and function of G-CSF and its receptor, the remainder of this review is focused on: (i) effects of G-CSF on the cells of the adaptive and innate immune systems; (ii) mechanisms by which this cytokine promotes tumor progression and invasion; and (iii) current clinical applications and potential risks of the use of rG-CSF in medical oncology.